2020
DOI: 10.1002/gps.5425
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated framework for advancing implementation science for the implementation process and adherence assessment of a non‐pharmacological delirium prevention program

Abstract: ObjectiveTo evaluate the contribution of applying the theoretical framework of implementation science for adherence to non‐pharmacological interventions to prevent delirium.MethodsA quasi‐experimental prospective design was conducted from March 2017 to October 2018 in a teaching hospital. Participants included 149 healthcare staff and 72 elderly inpatients. A non‐pharmacological delirium prevention program was designed, applied and evaluated in accordance with the consolidated framework for advancing implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 39 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The implementation studies targeted a range of health professionals including physicians [ 41 ], surgeons [ 42 44 ], anaesthesiologists [ 43 , 44 ], medical staff [ 45 52 ], nurses [ 41 45 , 47 62 ], nurse assistants [ 47 , 48 , 57 , 61 ], dietitians [ 42 , 48 , 52 , 61 ], physical therapists [ 47 , 50 , 59 , 61 , 63 , 64 ], occupational therapists [ 50 , 59 , 61 ], psychologists [ 50 ], multidisciplinary teams [ 42 , 47 , 50 , 52 , 61 , 65 , 66 ], as well as support services team members including food service staff, [ 49 ] and biomedical and sterile processing technicians. [ 43 ] Studies targeting more than one professional group or multidisciplinary teams more often used a determinant framework or a combination of more than one framework (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation studies targeted a range of health professionals including physicians [ 41 ], surgeons [ 42 44 ], anaesthesiologists [ 43 , 44 ], medical staff [ 45 52 ], nurses [ 41 45 , 47 62 ], nurse assistants [ 47 , 48 , 57 , 61 ], dietitians [ 42 , 48 , 52 , 61 ], physical therapists [ 47 , 50 , 59 , 61 , 63 , 64 ], occupational therapists [ 50 , 59 , 61 ], psychologists [ 50 ], multidisciplinary teams [ 42 , 47 , 50 , 52 , 61 , 65 , 66 ], as well as support services team members including food service staff, [ 49 ] and biomedical and sterile processing technicians. [ 43 ] Studies targeting more than one professional group or multidisciplinary teams more often used a determinant framework or a combination of more than one framework (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…No study detailed the rationale or criteria used for selecting a specific theoretical implementation framework over another. Fidelity to the implementation strategy was generally not reported, or when included was frequently limited to compliance with attending training or education sessions [ 47 , 51 , 53 , 58 , 61 ]. Only three studies reported overall compliance with the implementation approach [ 45 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…21 However, it is important to take into account that to modify behaviors in healthcare professionals, it is necessary not only to modify knowledge but also, and more importantly, to invoke changes in the beliefs and attitudes of health personnel that are sustainable over time. 34…”
Section: Resultsmentioning
confidence: 99%
“…21 However, it is important to take into account that to modify behaviors in healthcare professionals, it is necessary not only to modify knowledge but also, and more importantly, to invoke changes in the beliefs and attitudes of health personnel that are sustainable over time. 34 The presence, intensity, and duration of hospital delirium negatively affect the nursing workload and quality of care since people with delirium required an average of 60 additional minutes of attention. 44 However, preventive interventions go beyond identifying patients at risk, affecting the structure of the hospital and the organizational issues of care.…”
Section: The Quality Of Hospital Carementioning
confidence: 99%
“…Before this clinical trial, local pilot studies have shown some progress in this area. It has been reported that the incorporation of software technology through a "PREVEDEL" tablet is feasible and can be implemented on a hospital level, with possible effects on decreasing delirium [ 12 ] and the implementation of nPPD following a theoretical model improves the adherence of health personnel [ 13 ].…”
Section: Introductionmentioning
confidence: 99%